An Immature Type II Dens Invaginatus in a Mandibular Lateral Incisor with Talon's Cusp: A Clinical Dilemma to Confront - Anshul Gangwar; Deepa Singal; K. Y. Giri; Anshita Agarwal; S. Sruthi Keerthi (Hindawi Limited, 2014)
Dens invaginatus (DI) is a malformation of teeth probably resulting from an infolding of the dental papilla during tooth development. DI is classified as type I, II, and III by Oehlers depending on the severity of malformation. The maxillary lateral incisor is the most commonly affected tooth. Structural defects do exist in the depth of the invagination pits, and as a consequence, the early development of caries and the subsequent necrosis of the dental pulp, as well as abscess and cyst formation are clinical implications associated with DI. Occasionally, we can see more than one developmental anomaly occurring in a single tooth. In such cases it becomes important to identify the anomalies and initiate a proper treatment plan for good prognosis. In this paper, an unusual case of DI which clinically presented as a huge talons cusp affecting a mandibular lateral incisor tooth is described. This case report illustrates grinding of the talons cusp followed by nonsurgical endodontic management of dens invaginatus type II with an immature apex and periapical lesions, in which Mineral Trioxide Aggregate (MTA) shows a complete periapical healing with bone formation at the site of the lesions.